Studies on Lipid Content and Composition in Banded Coral Shrimp (Stenopus Hispidus) Embryos. Issue 5 (1st September 2015) - Wang, Li-Hsueh; Lin, Chiahsin; Huang, Chi-Yang; Tsai, Sujune
Abstract: Poor harvest practices of marine shrimps sometimes cause severe damage to the coral reefs. Availability of cryo-preserved embryos would considerably reduce coral reef damage. To develop low temperature preservation for shrimp embryos, this study assessed the lipid content and composition in the embryos of Stenopus hispidus (Olivier, 1811 ). The results showed that the main lipids in S. hispidus embryos include wax ester, triacylglycerol, free fatty acids, phosphatidylethanolamine, and phosphatidylcholine. The predominant lipid in the eye-development, heartbeat, and pre-hatch stages of S. hispidus embryos was phosphatidylethanolamine, followed by phosphatidylcholine, fatty acids, wax ester, and triacylglycerol. Lipid concentration in the embryos in the pre-hatch stage was significantly lower than that in the other two stages. Phosphatidylethanolamine, phosphatidylcholine, and free fatty acids concentrations in the embryos were significantly higher in the eye-development stage than in the heartbeat and pre-hatch stages. However, all three developmental stages had low wax ester and triacylglycerol concentrations. The lower lipid concentration in the embryos in the pre-hatch stage compared with the eye-development and heartbeat stages make them more tolerant to low temperatures. Embryos in the pre-hatch stage have well-developed structures and thus are better candidates for shrimp embryo cryopreservation research.